Islamic Paradigm Towards Cultural Acculturation In the Belamin Tradition Among the Nobles of the Matan Tanjungpura Kingdom - Husnun - Nahdhiyyah; Agung Setiawan (The Pontianak State Institute of Islamic Studies, 2022)
This study aims to determine the meaning of cultural acculturation in the Belamin tradition and the Islamic paradigm of cultural acculturation among the nobles of the Matan Tanjungpura Kingdom. The research method used is a literature review with an interpretative symbolic approach. Belamin tradition is a construct of humanity that has been formed from the time of the ancestors in the descendants of the Matan Tanjungpura Kingdom which in interpretive symbolic language is a cognitive system (pattern Of), and then regeneratively occurs cultural agreement and the local community based on the times with the entry of Islam in the Matan Tanjungpura Kingdom until became a legitimate tradition and was referred to a value system (Pattern For). The legitimized belamin tradition is an acculturation of Hindu and Islamic culture that should not be abandoned by noble families because it is attached to a myth which is part of the cognitive system in interpretative symbolic language, which then results in a compromise encounter to form a culture called a system of meaning in interpretive symbolic language. Islam argues that all stages and processions of cultural acculturation in the belamin tradition may be preserved and maintained as long as the tradition has benefits and does not cause harm (negative effects), not related to technical worship, and as long as there are no qath'iy texts that prohibit it.